2004
DOI: 10.1046/j.1600-6143.2003.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

New Onset Diabetes Mellitus in Patients Receiving Calcineurin Inhibitors: A Systematic Review and Meta-Analysis

Abstract: New onset diabetes mellitus (NODM) is a serious complication of transplantation. This meta-analysis evaluates the reported incidence of NODM after solid organ transplantation in patients receiving CNI treatment.Databases from January 1992 to April 2002 were searched. Fifty-six publications providing NODM incidence data were reviewed. Sixteen prospective, randomized comparative studies providing information on incidence of insulin-dependent diabetes mellitus (IDDM) were subjected to meta-analysis.New onset diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
292
3
18

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(332 citation statements)
references
References 94 publications
19
292
3
18
Order By: Relevance
“…In the analysis performed by Montori et al (3), the type of immunosuppressive regimen used was found to explain 74% of the variability in incidence, with high-dose steroids being associated with the highest incidences. Aside from steroids (8), the calcineurin inhibitors (CNI) are associated with an increased risk for diabetes after transplantation, the risk being higher for tacrolimus than for cyclosporine A (CsA) (3,4,9).…”
mentioning
confidence: 99%
“…In the analysis performed by Montori et al (3), the type of immunosuppressive regimen used was found to explain 74% of the variability in incidence, with high-dose steroids being associated with the highest incidences. Aside from steroids (8), the calcineurin inhibitors (CNI) are associated with an increased risk for diabetes after transplantation, the risk being higher for tacrolimus than for cyclosporine A (CsA) (3,4,9).…”
mentioning
confidence: 99%
“…National registry analyses suggest that 15 to 20% of renal transplant patients who do not have diabetes and receive a CNI currently develop NOD within 1 yr of transplantation (2,3). Among clinical trials, which tend to use more restrictive criteria for NOD, the incidence is estimated to be 10 to 15% (7). Studies have examined the linkage between two CNI (cyclosporine [CsA] and tacrolimus [Tac]) and the development of NOD.…”
mentioning
confidence: 99%
“…After kidney transplantation, BMI tends to increase due to various factors, including the improvement of general condition and the effect of glucocorticoids (Clunk et al 2001). Furthermore, in addition to an increase in BMI, successful kidney transplant recipients have a predisposition to develop diabetes due to use of corticosteroids (Hjelmesaeth et al 1997;Hjelmesaeth et al 2001;Luan et al 2011) and CNI (Woodward et al 2003;Heisel et al 2004;Webster et al 2005;Shah et al 2006;Ekberg et al 2007;Vincenti et al 2007). Therefore, transplant recipients are a vulnerable population amenable to intervention for prevention of NODAT.…”
Section: Discussionmentioning
confidence: 99%
“…A number of risk factors have been suggested to predict the development of NODAT: the recipient's older age (Cosio et al 2001;Kasiske et al 2003;Hoitsma and Hilbrands 2006;Shah et al 2006;Kuypers et al 2008), use of tacrolimus (Woodward et al 2003;Heisel et al 2004;Webster et al 2005;Hoitsma and Hilbrands 2006;Shah et al 2006;Ekberg et al 2007;Vincenti et al 2007), high pretransplant oral glucose tolerance test (OGTT) values (Bergrem et al 2010), and obesity (Kasiske et al 2003;Shah et al 2006;Joss et al 2007). Among these, obesity is likely to be an important therapeutic target because it can be safely modified by lifestyle-change intervention, including dietary modification and exercise.…”
Section: Introductionmentioning
confidence: 99%